The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4314/njp.v42i1.13
|View full text |Cite
|
Sign up to set email alerts
|

The performance of an Histidine rich protein-2 rapid diagnostic test (RDT) against the standard microscopy in the diagnosis of malaria parasitaemia among febrile under-five children at Nnewi

Abstract: standard, the sensitivity of the RDT was 80%, the specificity was 93.8%. The positive and negative predictive values were 76.2% and 94.9% respectively. Conclusion: Based on these findings, the RDT demonstrated reasonable concordance with microscopy and was recommended for use at every level of healthcare in the diagnosis of malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
1
7
1
Order By: Relevance
“…The overall prevalence of malaria observed in this study suggests that malaria is still a major cause of childhood morbidity. A slightly lower prevalence of 20% was reported in the rainy season of the year 2014 at the same study site, which compares to 23.3% seen in this study [ 5 ]. This shows a near uniform transmission in the study locale.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…The overall prevalence of malaria observed in this study suggests that malaria is still a major cause of childhood morbidity. A slightly lower prevalence of 20% was reported in the rainy season of the year 2014 at the same study site, which compares to 23.3% seen in this study [ 5 ]. This shows a near uniform transmission in the study locale.…”
Section: Discussioncontrasting
confidence: 67%
“…The minimum number of children enrolled in this study was calculated using the Cochran formula for calculation of sample size based on a confidence interval of 95% which is equivalent to a confidence coefficient of 1.96, malaria prevalence of 20% in febrile children [ 5 ] and a non-response rate of 5%. This gave a minimum sample size of 246.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sensitivity of 29% in this study is far below that obtained by researchers like Ezeudu at the children’s out-patient clinic and children’s emergency room of Nnamdi Azikiwe University Teaching Hospital (NAUTH) Nnewi, Nigeria, who reported a sensitivity and specificity of 80% and 93.8%, respectively. 17 Xiaodong et al 18 in China also found that the CareStat rapid diagnostic test had a sensitivity of 89.68% and a specificity of 98.26% compared to the gold standard microscopy method for the detection of malaria. Variations in sensitivity between the different studies may be attributed to differences in the types of RDTs used or test methodology and skills of the microscopist.…”
Section: Discussionmentioning
confidence: 98%
“…This rapid proliferation of brands also lead to increase in the number of substandard products, which easily find their way into developing countries like Nigeria with less stringent quality control. Reviews and studies show that the commercially available MRDTs show wide variability in diagnostic sensitivity and specificity [21][22][23][24][25]. To stem this "influx," WHO has continued to conduct testing of the products and issuing guidelines to assist countries adopt the mRDT for use [20].…”
Section: Current Topics In Malaria 76mentioning
confidence: 99%